2022
DOI: 10.1111/ajgw.12545
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofBotrytis cinerea‐infected grapes on quality parameters of red wine made from withered grapes

Abstract: Background and Aims: Modification of important odorants induced by Botrytis cinerea has been reported in dry red wine (Amarone) made from withered grapes, but the impact on wines produced in other regions remains to be elucidated. Methods and Results: Cabernet Franc grapes from Ontario were dried to 28.0 Brix and fermented with either nonbotrytised grapes or a combination of non-botrytised and botrytised grapes (10% infection). The metabolites, including volatile compounds, were analysed and sensory evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…The results of the ANOVA based on overall liking scores of the three identified clusters for the consumer acceptance test coincide qualitatively with the results reported in the literature by Kelly et al (2022). These authors also found a cluster named “likes everything” (dominated by females 52%), and the two other clusters were dominated by a preference for one of the tasted wines.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the ANOVA based on overall liking scores of the three identified clusters for the consumer acceptance test coincide qualitatively with the results reported in the literature by Kelly et al (2022). These authors also found a cluster named “likes everything” (dominated by females 52%), and the two other clusters were dominated by a preference for one of the tasted wines.…”
Section: Resultssupporting
confidence: 89%
“…In particular, previous research yielded several styles of wines obtained following different Roman protocols (Harutyunyan et al, 2022). Their appreciation may be similar to wines produced from overripe grapes (Sancho‐Galán, Amores‐Arrocha, Palacios, & Jiménez‐Cantizano, 2022), raisins (Ruiz‐Bejarano, Durán‐Guerrero, Castro, Barroso, & Rodríguez‐Dodero, 2020), withered grapes (Tomasi et al, 2021; Zapparoli et al, 2018), or partially dehydrated grapes (Kelly et al, 2018; Kelly, Inglis, Dowling, & Pickering, 2022; Kelly, Inglis, & Pickering, 2020). However, the wine production techniques and grapes reported in these works differ from the recreated ancient wines described by Harutyunyan et al (2022).…”
Section: Introductionmentioning
confidence: 87%
“…In addition, it is essential to consider that climate change can affect the spread of diseases and pests that can damage vineyards. Increased humidity and heat can contribute to the development of fungal diseases such as mildew and botrytis (Kelly et al, 2022).…”
Section: Introductionmentioning
confidence: 99%